Expanded graphite and preparation method thereof

Through a new preparation method, the reaction of waste graphite with specific chemical agents and high-temperature expansion treatment is used to solve the problem of poor electrochemical performance of expanded graphite in supercapacitors, and excellent specific capacitance and long cycle performance are achieved, which improves its application prospects.

CN119569050AInactive Publication Date: 2025-03-07GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411588518.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When applied to supercapacitors, expandable graphite has poor electrochemical performance, resulting in limited application.

Method used

A preparation method is adopted, which includes mixing waste graphite with sodium nitrate, concentrated sulfuric acid and potassium permanganate, undergoing oil bath heat treatment and oxidation intercalation treatment, and then undergoing high-temperature expansion treatment to obtain expanded graphite with excellent specific capacitance and long cycle performance.

Benefits of technology

The expanded graphite prepared as the electrode material of the supercapacitor showed excellent specific capacitance and long cycle performance. After cycling for 10,000 cycles, the capacity retention rate was greater than 80%, which significantly improved the electrochemical performance of the expanded graphite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569050A_ABST
    Figure CN119569050A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon materials, and particularly relates to expanded graphite and a preparation method thereof. In order to improve the electrochemical performance displayed when the expanded graphite is currently applied to a supercapacitor, the method comprises the following steps: firstly, carrying out oil bath heating treatment on waste graphite by utilizing sodium nitrate, concentrated sulfuric acid and potassium permanganate, then carrying out oxidation intercalation treatment by utilizing hydrogen peroxide to obtain natural crystalline flake graphite, then washing and drying to treat the natural crystalline flake graphite into graphite oxide, and finally, preparing the expanded graphite into the supercapacitor. And finally, carrying out high-temperature expansion treatment to obtain the expanded graphite. The expanded graphite prepared by the method is used as an electrode material of a supercapacitor, the assembled supercapacitor shows excellent specific capacitance and excellent long cycle performance, and after 10000 cycles, the capacity retention ratio is greater than 80%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon materials, and in particular relates to expanded graphite and a preparation method thereof. Background Art

[0002] Expanded Graphite (EG) is a porous worm-like material obtained by chemical and heat treatment of natural flake graphite. This material not only retains the heat resistance, corrosion resistance, electrical conductivity, thermal conductivity, and self-lubrication of natural graphite, but also has additional properties such as lightness, softness, compressibility, and resilience. It can be widely used in electrode materials, oil absorption, fire retardant, oil absorption materials, environmental protection, medical dressings, and antistatic coatings.

[0003] At present, the methods for preparing expandable graphite mainly include chemical oxidation, electrochemical method, gas diffusion method, mixed liquid phase method, melting method, pressurization method, explosion method, catalyst method, photochemical method, etc. Among them, chemical oxidation is the most commonly used preparation method at present. The method is simple to operate and easy to control the reaction conditions. Compared with other methods, the equipment requirements are relatively low, the production cost is relatively low, and the controllability is strong. The interlayer spacing and oxidation degree of oxidized graphite can be effectively controlled to prepare expanded graphite with different properties. The method mainly includes two process steps: oxidation intercalation and expansion. In the oxidation intercalation step, natural flake graphite is mixed with strong acid and strong oxidant, and then chemically or electrochemically treated to form expandable graphite; in the expansion step, the expandable graphite expands rapidly at high temperature to form EG.

[0004] Expanded graphite has become an important choice of supercapacitor electrode material due to its advantages such as high specific surface area, excellent electrical conductivity and good mechanical flexibility. However, the electrochemical performance of expanded graphite when currently used in supercapacitors is poor, resulting in limited application. For this reason, the present invention is proposed. Summary of the invention

[0005] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides an expanded graphite and a preparation method thereof, wherein the expanded graphite has excellent specific capacitance and excellent long cycle performance, and improves the electrochemical performance exhibited by the expanded graphite when applied to supercapacitors.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A first aspect of the present invention provides a method for preparing expanded graphite, the method comprising the following steps:

[0008] S1. Dissolve waste graphite and sodium nitrate in concentrated sulfuric acid, then add potassium permanganate in an ice bath, transfer to 30-40°C, stir for 1-3h, and then add water;

[0009] S2, heating the mixed solution obtained in S1, and then adding water and hydrogen peroxide to change the mixed solution from brown-red to golden yellow;

[0010] S3. Washing and drying the mixed solution obtained in S2 to obtain expandable graphite, and then transferring the expandable graphite to an oxygen-free condition for high-temperature expansion treatment to obtain expanded graphite.

[0011] The expanded graphite prepared by the method of the present invention is used as an electrode material for a supercapacitor. The assembled supercapacitor exhibits excellent specific capacitance (the specific capacitance can be as high as 98.1 F / g at 1 A / g) and excellent long cycle performance. After 10,000 cycles, the capacity retention rate is greater than 80%, and the supercapacitor has important application prospects.

[0012] Preferably, in S1, the mass ratio of the waste graphite to sodium nitrate is 2:1, and the dosage ratio of the waste graphite to concentrated sulfuric acid is 1 g: 20-30 mL.

[0013] Preferably, in S1, the mass ratio of the waste graphite to potassium permanganate is 1-2:2-4.

[0014] Preferably, in S1, the potassium permanganate is slowly added within 60 minutes, and the addition rate of the potassium permanganate is 0.03-0.07 g / min.

[0015] Preferably, in S1, the usage ratio of the waste graphite and water is 1 g:40-60 mL.

[0016] Preferably, the usage ratio of the waste graphite and hydrogen peroxide is 1g:15-30mL, and the volume ratio of the water and hydrogen peroxide in S2 is 6-8:1.

[0017] Preferably, in S2, the temperature of the heating treatment is 90-100°C and the time is 20-40 minutes.

[0018] Preferably, in S3, the high-temperature puffing treatment is carried out under nitrogen, the treatment temperature is 600-900°C, the heating rate is 5-10°C / min, and the insulation time is 2-4h.

[0019] More preferably, the temperature of the high temperature expansion treatment is 700-900°C, the heating rate is 10°C / min, and the holding time is 3h. When the expanded graphite prepared under this condition is used as an electrode material for a supercapacitor, the assembled supercapacitor exhibits excellent specific capacitance (specific capacitance at 1A / g is 84.575-98.1F / g) and excellent long cycle performance. After 10,000 cycles, the capacity retention rate is greater than 80%.

[0020] Preferably, in S3, the drying temperature is 55-65° C., and the drying time is 10-15 hours.

[0021] The second aspect of the present invention also provides expanded graphite prepared by the preparation method described in the first aspect.

[0022] The third aspect of the present invention further provides the use of the expanded graphite described in the second aspect in a supercapacitor.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The invention discloses a method for preparing expanded graphite, which comprises the steps of firstly performing oil bath heating treatment on waste graphite using sodium nitrate, concentrated sulfuric acid and potassium permanganate, then performing oxidation intercalation treatment using hydrogen peroxide to obtain natural flake graphite, then washing and drying the graphite to convert it into oxidized graphite, and finally performing high temperature expansion treatment to obtain expanded graphite. The expanded graphite prepared by the method of the invention has excellent electrochemical properties, and the supercapacitor assembled by using the expanded graphite as the electrode material of a supercapacitor exhibits excellent specific capacitance and excellent long cycle performance, and the capacity retention rate is greater than 80% after 10,000 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a flow chart for the preparation of expanded graphite;

[0026] Figure 2 is a scanning electron microscope image of the expanded graphite of Example 6;

[0027] Figure 3 is a scanning electron microscope image of the expanded graphite of Example 6;

[0028] Figure 4 is the specific capacitance of the capacitor when the expanded graphite of Examples 1-6 is used as the working electrode;

[0029] Figure 5 The cycle performance of the capacitor when the expanded graphite of Example 6 is used as the working electrode. DETAILED DESCRIPTION

[0030] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0031] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0032] Example 1: A method for preparing expanded graphite

[0033] like Figure 1 As shown, the preparation process includes the following steps:

[0034] (1) At room temperature, 1 g of waste graphite and 0.5 g of sodium nitrate were weighed and dissolved in 23 mL of 98% concentrated sulfuric acid, and mixed evenly to obtain a mixed solution A;

[0035] (2) Under ice bath conditions, weigh 3 g of potassium permanganate and slowly add it to the mixed solution A of step (1) over 60 min, followed by magnetic stirring in a 35° C. water bath for 2 h to obtain a mixed solution B;

[0036] (3) At room temperature, 46 mL of deionized water was slowly added to the mixed solution B in step (2) to obtain a mixed solution C;

[0037] (4) heating the mixed solution C of step (3) under oil bath conditions, slowly raising the temperature to 98° C. and maintaining the temperature for 30 min to obtain a mixed solution D;

[0038] (5) Add 140 mL of deionized water and 20 mL of hydrogen peroxide to the mixed solution D of step (4), and change the mixed solution D from brown-red to golden yellow;

[0039] (6) placing the solution after the reaction in step (5) in a centrifuge and washing it twice with deionized water and anhydrous ethanol in sequence to obtain a mixture;

[0040] (7) placing the mixture of step (6) in an oven at 60° C. and drying for 12 h to obtain expandable graphite;

[0041] (8) The expandable graphite is placed in a muffle furnace, high-purity nitrogen is introduced, and the temperature is raised to 600°C at a rate of 10°C / min. After being kept at this temperature for 3 hours, the furnace is cooled to room temperature and taken out to obtain the expanded graphite.

[0042] Example 2: A method for preparing expanded graphite

[0043] Compared with Example 1, the difference is that the heating rate in step (8) of Example 2 is 8°C / min.

[0044] Example 3: A method for preparing expanded graphite

[0045] Compared with Example 1, the difference is that the heating rate in step (8) of Example 3 is 5°C / min.

[0046] Example 4: A method for preparing expanded graphite

[0047] Compared with Example 1, the difference is that step (8) of Example 4 is to increase the temperature to 700° C. and keep it for 3 hours.

[0048] Example 5: A method for preparing expanded graphite

[0049] Compared with Example 1, the difference is that step (8) of Example 5 is to increase the temperature to 800° C. and keep it for 3 hours.

[0050] Example 6: A method for preparing expanded graphite

[0051] Compared with Example 1, the difference is that step (8) of Example 6 is to raise the temperature to 900° C. and keep it for 3 hours.

[0052] Scanning electron microscopy (SEM) confirmed that Examples 1-6 were able to successfully prepare expanded graphite. The expanded graphite was worm-like in appearance. A graphite worm was composed of a plurality of "microcells" connected together. There were many tiny pores in the microcells, forming a rich pore structure of the expanded graphite (the SEM morphology of some expanded graphite is shown in FIG. Figure 2 , 3 shown).

[0053] Experimental example: Electrochemical performance test

[0054] The expanded graphite prepared in Example 1-6 was used as the working electrode, and a three-electrode system was selected to test its electrochemical performance, and the specific capacitance was calculated for comparison, wherein the electrolyte was 6M KOH, the reference electrode was HgO, the counter electrode was a platinum sheet, and the electrochemical workstation used was the CHI600E workstation of Shanghai Chenhua.

[0055] The specific preparation method of the working electrode is as follows:

[0056] (1) Cut the nickel foam electrode sheet into 1.2×4 cm pieces and place them in a beaker;

[0057] (2) Add acetone to cover the beaker, sonicate at 99% power for 5 min, remove the solution, and then add deionized water and anhydrous ethanol in sequence and repeat the above steps;

[0058] (3) Blow the nickel foam electrode sheet with cold air for 10 seconds after ultrasonic treatment, and then dry it in an oven at 60°C for 12 hours;

[0059] (4) The dried sample in step (3) is mixed with a conductive agent (superconducting carbon black) and a binder (polyvinylidene fluoride) in a mass ratio of 8:1:1 and dissolved in N-methylpyrrolidone (NMP), and the mixture is further ground until it becomes sticky and particle-free. Finally, the obtained slurry is applied to one-third of the long end edge of the nickel foam electrode sheet and folded;

[0060] (5) The folded sample is kept at 15 kPa for 20 s for tableting;

[0061] (6) The sample in step (5) is placed in a 60°C oven and dried for another 12 hours to obtain the working electrode in the three-electrode system.

[0062] The test results are shown in Table 1 and Figure 4 As shown in Table 1 and Figure 4 From the experimental data we can see that:

[0063] It can be seen from Examples 1 and 2-3 that, under the premise that other experimental conditions and steps remain unchanged, as the heating rate increases during the expansion process, the performance of the prepared expanded graphite is better, much higher than the expanded graphite prepared at a heating rate of 5°C / min and 8°C / min. This shows that when the heating rate during the expansion process is 10°C / min, the supercapacitor assembled with the expanded graphite prepared at this time as the electrode material of the supercapacitor exhibits a better specific capacitance (91.55F / g at 1A / g).

[0064] It can be seen from Examples 1 and 4-6 that, under the premise that other experimental conditions and steps remain unchanged, as the maximum temperature reached during the expansion process increases, the specific capacitance of the prepared expanded graphite as the electrode material of the supercapacitor first decreases and then increases. When the maximum temperature reaches 900°C, the specific capacitance of the assembled supercapacitor is greater than 95F / g. This shows that when the maximum temperature reached during the expansion process is 900°C, the assembled supercapacitor using the expanded graphite prepared at this time as the electrode material of the supercapacitor exhibits the most excellent specific capacitance (98.1F / g at 1A / g) and exhibits excellent long cycle performance. After 10,000 cycles, the capacity retention rate is greater than 80% ( Figure 5 ).

[0065] It can be seen that when the expanded graphite prepared by the method of the present invention is used as an electrode material for a supercapacitor, the assembled supercapacitor exhibits excellent electrochemical properties, not only has excellent specific capacitance, but also has excellent long cycle performance, which improves the electrochemical properties exhibited by the expanded graphite when applied to the supercapacitor, and has important application prospects.

[0066] Table 1 Specific capacitance of capacitors using the expanded graphite of Examples 1-6 as working electrodes

[0067]

[0068] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing expanded graphite, characterized in that: The following steps are involved: S1. Dissolve waste graphite and sodium nitrate in concentrated sulfuric acid, then add potassium permanganate in an ice bath, transfer to 30-40°C, stir for 1-3h, and then add water; S2, heating the mixed solution obtained in S1, and then adding water and hydrogen peroxide to change the mixed solution from brown-red to golden yellow; S3. Washing and drying the mixed solution obtained in S2 to obtain expandable graphite, and then transferring the expandable graphite to an oxygen-free condition for high-temperature expansion treatment to obtain expanded graphite.

2. A method for preparing expanded graphite according to claim 1, characterized in that, In S1, the mass ratio of the waste graphite to sodium nitrate is 2:1, and the dosage ratio of the waste graphite to concentrated sulfuric acid is 1 g: 20-30 mL.

3. A method for preparing expanded graphite according to claim 1, characterized in that, In S1, the mass ratio of the waste graphite to potassium permanganate is 1-2:2-4.

4. The method for preparing expanded graphite according to claim 1, characterized in that: In S1, the potassium permanganate is slowly added within 60 minutes, and the addition rate of the potassium permanganate is 0.03-0.07 g / min.

5. The method for preparing expanded graphite according to claim 1, characterized in that: In S1, the usage ratio of the waste graphite and water is 1g:40-60mL.

6. The method for preparing expanded graphite according to claim 1, characterized in that: The usage ratio of the waste graphite and hydrogen peroxide is 1g:15-30mL, and the volume ratio of water to hydrogen peroxide in S2 is 6-8:

1.

7. The method for preparing expanded graphite according to claim 1, characterized in that: In S2, the heating treatment is performed at a temperature of 90-100°C and for a time of 20-40 minutes.

8. The method for preparing expanded graphite according to claim 1, characterized in that: In S3, the high temperature puffing treatment is carried out under nitrogen, the treatment temperature is 600-900°C, the heating rate is 5-10°C / min, and the insulation time is 2-4h.

9. Expanded graphite prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the expanded graphite according to claim 9 in supercapacitors.

Citation Information

Patent Citations

  • High-reversible-capacity sodium-ion battery negative electrode material, method for preparing high-reversible-capacity sodium-ion battery negative electrode material from large flake graphite and application of high-reversible-capacity sodium-ion

    CN116477620A